Antropopedra: uma espacialidade ressonante. - Guedes, Thiago Matheus Costa (2018)
Submitted by Simone Maisonave (simonemaisonave@hotmail.com) on 2018-05-18T16:33:08Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Thiago Matheus Costa Guedes_Dissertação.pdf: 37276868 bytes, checksum: d2b07f76387213c36054d9db04c90024 (MD5)